RIG “AB-1” Specification Study on “Batara” Well Based on Drawworks, Hook Load and Mud Pump Data - Nijusiho Manik; Rohima Sera Afifah; Andi Jumardi; Fatma; M. Rizal Faahrun; Zavta Rizki; Darmiyati, Iin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The analysis conducted in this study focuses on the